2022
DOI: 10.5552/drvind.2022.2104
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hygroscopic Thickness Swelling Rate of Hydrothermally Treated Beech Wood / Polypropylene Composites

Abstract: Long-term hygroscopic thickness swelling rate of polypropylene (PP) composites filled with thermally treated wood flour was investigated. The beech wood chips were heat treated at 120 °C, 150 °C or 180 °C for 30 or 120 min using saturated steam in a digester. The composites based on PP, beech wood flour (BF), and coupling agents (PP-g-MA) were made by melt compounding and injection molding. The weight ratio of BF to PP was controlled at 50/47 for all blends. The amount of coupling agent was fixed at 3 wt.% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The density and EMC values of the control specimens were higher than the heattreated samples. Arwinfar et al (2016) and Hosseinihashemi et al (2022) discuss the mechanical properties and long-term hygroscopic thickness swelling rate of heat-treated wood particle WPCs in different conditions; they found that the acceptable treatment to make the WPC was 150 °C for 30 minutes for mechanical strength; 120 °C for 30 min and 150 °C for 30 minutes for long-term hygroscopic thickness swelling rate. Moreover, the micromorphology images of the composites produced from the wood heated at the aforementioned conditions showed that there are considerably fewer pores and so broken fiber ends embedded in the matrix of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The density and EMC values of the control specimens were higher than the heattreated samples. Arwinfar et al (2016) and Hosseinihashemi et al (2022) discuss the mechanical properties and long-term hygroscopic thickness swelling rate of heat-treated wood particle WPCs in different conditions; they found that the acceptable treatment to make the WPC was 150 °C for 30 minutes for mechanical strength; 120 °C for 30 min and 150 °C for 30 minutes for long-term hygroscopic thickness swelling rate. Moreover, the micromorphology images of the composites produced from the wood heated at the aforementioned conditions showed that there are considerably fewer pores and so broken fiber ends embedded in the matrix of polymer.…”
Section: Introductionmentioning
confidence: 99%